Artesunate inhibits intestinal tumorigenesis through inhibiting wnt signaling. (25th July 2020) - Hamoya, Takahiro; Fujii, Gen; Iizumi, Yosuke; Narita, Takumi; Komiya, Masami; Matsuzawa, Yui; Miki, Kohei; Kondo, Tadashi; Kishimoto, Shinji; Watanabe, Kenji; Wakabayashi, Keiji; Sakai, Toshiyuki; et al.
Abstract: Artesunate (ART) is a clinically approved antimalarial drug and was revealed as a candidate of colorectal cancer chemopreventive agents in our drug screening system. Here, we aimed to understand the suppressive effects of ART on intestinal tumorigenesis. In vitro, ART reduced T-cell factor/lymphoid enhancer factor (TCF/LEF) promoter transcriptional activity. In vivo, ART inhibited intestinal polyp development. We found that ART reduces TCF1/TCF7 nuclear translocation by binding the Ras-related nuclear protein (RAN), suggesting that ART inhibits TCF/LEF transcriptional factor nuclear translocation by binding to RAN, thereby inhibiting Wnt signaling. Our results provide a novel mechanism through which artesunate inhibits intestinal tumorigenesis. Abstract : Artesunate prevents nuclear translocation of an important transcription factor related to Wnt signaling by binding the Ras-related nuclear protein (RAN).